2021
DOI: 10.3389/fphar.2021.758792
|View full text |Cite|
|
Sign up to set email alerts
|

C1q/TNF-Related Protein 9 Attenuates Atherosclerosis by Inhibiting Hyperglycemia-Induced Endothelial Cell Senescence Through the AMPKα/KLF4 Signaling Pathway

Abstract: Hyperglycemia-induced endothelial cell senescence has been widely reported to be involved in the pathogenesis of type 2 diabetes mellitus‒accelerated atherosclerosis. Thus, understanding the underlying mechanisms and identifying potential therapeutic targets for endothelial cell senescence are valuable for attenuating atherosclerosis progression. C1q/tumor necrosis factor-related protein 9 (CTRP9), an emerging potential cardiokine, exerts a significant protective effect with respect to atherosclerosis, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…The inflammation, ROS overproduction, and advanced glycation end-products (AGEs) caused by hyperglycemia were considered as major contributors to the complications’ etiologically, as they impair vascular function directly [ 19 ]. On the other hand, inflammation, ROS, and AGEs are well-known to promote cellular senescence, and actually, hyperglycemia-induced endothelial cell senescence was observed in vascular cells, such as endothelial cells [ 10 , 20 , 21 , 22 , 23 ], smooth muscle cells [ 11 ], endothelial progenitor cells [ 12 ], and mesenchymal stem cells [ 13 ]. These observations suggest that senescence may be serving as a shared downstream link to diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammation, ROS overproduction, and advanced glycation end-products (AGEs) caused by hyperglycemia were considered as major contributors to the complications’ etiologically, as they impair vascular function directly [ 19 ]. On the other hand, inflammation, ROS, and AGEs are well-known to promote cellular senescence, and actually, hyperglycemia-induced endothelial cell senescence was observed in vascular cells, such as endothelial cells [ 10 , 20 , 21 , 22 , 23 ], smooth muscle cells [ 11 ], endothelial progenitor cells [ 12 ], and mesenchymal stem cells [ 13 ]. These observations suggest that senescence may be serving as a shared downstream link to diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that senescence may be serving as a shared downstream link to diabetic complications. Since the endothelial cell is critical to vascular functions, including the maintenance of vessel integrity, secretion, and participation of immune response [ 24 ], and is directly exposed to high glucose in T2DM, the senescent endothelial cell may have a profound impact on the pathogenesis of diabetic complications [ 20 , 21 , 22 , 23 ]. HUVEC is a widely used cellular model to investigate the regulation of endothelial function, for example, senescence and angiogenesis [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in developmentally regulated GTP-binding protein 2 (DRG2) increases NOX2 expression, ROS generation, and senescence in ECs [ 142 ]. C1q/tumor necrosis factor-related protein 9 (CTRP9), an emerging potential cardiokine, contributes to the inhibition of hyperglycemia-induced endothelial senescence through an AMPKα/ Krüppel-like factor 4 (KLF4)-dependent signaling pathway [ 143 ]. Soluble dipeptidyl peptidase 4 (DPP4), secreted from visceral adipose tissue, induces EC senescence through the protease-activated receptor 2 (PAR2)–cyclooxygenase2 (COX-2)–thromboxane receptor (TP) axis and activates the NLRP3 inflammasome [ 144 ].…”
Section: Molecular Players and Pathways Associated With Endothelial C...mentioning
confidence: 99%
“…Kim et al reported that tetraspanin‐29 (CD9) aggravates atherosclerotic plaque formation by inducing endothelial cell senescence, while CD9 knockdown or CD9 antibody treatment can noticeably prevent it in apolipoprotein E (ApoE)−/− mice and Ldlr−/− mice [22, 26]. Hou et al found that CTRP9 inhibited hyperglycemia‐induced endothelial cell senescence and reduced atherosclerotic plaque formation in vivo [27]. In addition, Xiong et al reported that overexpression of the circular RNA circGNAQ inhibited the senescence of VECs and the development of AS in vivo and in vitro [23].…”
Section: Introductionmentioning
confidence: 99%